2021
DOI: 10.1021/acsomega.1c02801
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of α-Alkyl Styrene Derivatives

Abstract: There is a significant need to develop more rapid and efficient routes to styrene derivatives, since they are extensively used in polymer sciences. This manuscript reports a one-pot synthesis of an array of α-alkyl styrene derivatives from readily available natural products (i.e., estragole and safrole). This method is regioselective, producing a rearranged adduct, under transition metal-free conditions. This methodology has broad nucleophile scope, even tolerating sterically hindered nucleophiles; it is gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Initially, it was found that allylaryl bearing electron poor and electron-neutral functional groups favors the formation of ( E )-allylic compounds such as ( E )-allylic azide 3 ( Scheme 1 ) [ 26 ]. On the other hand, in electron-rich systems (e.g., estragole or safrole), a dearomative rearrangement occurs to preferentially form adducts such as 4 (α-azidomethyl styrene) [ 27 ]. At the same time, it was also observed that the formation of regioisomers mainly occurred during the bromination step [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, it was found that allylaryl bearing electron poor and electron-neutral functional groups favors the formation of ( E )-allylic compounds such as ( E )-allylic azide 3 ( Scheme 1 ) [ 26 ]. On the other hand, in electron-rich systems (e.g., estragole or safrole), a dearomative rearrangement occurs to preferentially form adducts such as 4 (α-azidomethyl styrene) [ 27 ]. At the same time, it was also observed that the formation of regioisomers mainly occurred during the bromination step [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…5-(2,3-dibromopropyl)benzo[ d ][1,3]dioxole ( 2a ) was obtained in a 22% yield, while 5-(1,3-dibromopropan-2-yl)benzo[ d ][1,3]dioxole ( 2b ) was isolated in a 63% yield. 1,3-dibromide 2b was then reacted under our standard azidation conditions [ 26 , 27 ] using sodium azide as the nucleophile and 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) as the base. To our delight, the expected product [5-(3-azidoprop-1-en-2-yl)benzo[ d ][1,3]dioxole 4 ] was obtained in a 91% yield ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, we reported a straightforward protocol for the synthesis of a-alkyl styrenes (Scheme 1, eqn (3)). 39 It was observed that the bromination step plays a decisive role in determining the adduct regioselectivity and yield. Specifically, the bromination solvent and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported the synthesis of α-alkyl styrene using transition metal-free one-pot reaction conducted under mild conditions. Interestingly, this reaction resulted in a mixture of two distinct styrene derivatives, a and b (Scheme ). Based on the experimental observations in our previously reported work and the bromine-mediated rearrangement reaction studies done by Dubois and Costa, it was proposed that allylaryl undergoes an alkene bromination to form bromonium intermediate I , which later on undergoes an intramolecular rearrangement, a 1,2-shift by the electron-rich aryl moiety to form the spiro[2.5] intermediate II . , The spiro[2.5] intermediate II can be ring-opened by a nucleophilic attack by a Br – anion on the three-membered ring to produce either a 2,3-dibromo derivative ( a ) or a 1,3-dibromo derivative ( b ).…”
Section: Introductionmentioning
confidence: 99%